A filosofia e música: uma metodologia interdisciplinar no contexto de uma escola pública maranhense - PÁSCOA FILHO, João Ferreira da (2021)
The research refers to the challenges of teaching philosophy and also to the possibilities of developing an interdisciplinary methodology for teaching philosophy in the context of high school in Maranhão, at the interface with music. The research has as contextual perspective the place of the public school: C. E. Luís Augusto Barros, in the municipality of São Mateus do Maranhão. Its general objective is to develop new methods for teaching philosophy in public secondary education in a school in Maranhão, combining knowledge of philosophy with knowledge of art, especially music. This is a qualitative research in which we use the case study as a procedural method. The main research question was: what concrete contribution can music make to the construction of a methodology for teaching philosophy? It is important to stress that, given the pandemic moment, we decided not to hold face-to-face meetings with teachers and not even to use the product with students and teachers. In this sense, the product is presented as a methodological proposal. To achieve this goal, we have used theoretical contributions, data collection tools such as non participant and systematic observation and the questionnaire from a distance. The theoretical contributions that appear in the research include: Gainza (1988); Eisner (1991); Luckesi (1994); Millet (1997); Chauí (2000); Alves (2002); Gontijo and Valadão (2004); Aspis (2004); Fávero et al. (2004); Cauquelin (2005); Spider (2006); Rocha Jr. (2007); Noble and Earth (2007); Prendin (2009); Feitosa (2009); Rodrigo (2009); Gallo (2012); Silveira (2012); Neves (2013); and others. The final product of the research is an interdisciplinary methodological notebook entitled - Philosophizing with Music: Intebrdisciplinary Methodological Experience. It contains suggestions for topics that can help engage young people in philosophy. It counts for this with the contribution of music.